SARS-CoV-2 survival on skin and its transfer from contaminated surfaces - Ana K. Pitol; Samiksha Venkatesan; Siobhan Richards; Michael Hoptroff; Amitabha Majumdar; Grant L. Hughes (PLoS ONE, 2025)
Understanding the transmission dynamics of SARS-CoV-2, particularly its transfer from contaminated surfaces (fomites) to human skin, is crucial for mitigating the spread of COVID-19. While extensive research has examined the persistence of SARS-CoV-2 on various surfaces, there is limited understanding of how efficiently it transfers to human skin, and how long it survives on the skin. This study investigates two key aspects of SARS-CoV-2 transmission: (1) the transfer efficiency of SARS-CoV-2 from non-porous (plastic and metal) and porous (cardboard) surfaces to a 3D human skin model (LabSkin), and (2) the survival of SARS-CoV-2 on the skin under different temperature conditions. First, we validated LabSkin as a suitable surrogate for human skin by comparing the transfer efficiency of the bacteriophage Phi 6 from surfaces to LabSkin and to human volunteers’ fingers. No significant differences were observed, confirming LabSkin’s suitability for these studies. Subsequently, the transfer of SARS-CoV-2 from surfaces to LabSkin was assessed, showing that plastic and metal surfaces had similar transfer efficiencies (~13%), while no transfer occurred from cardboard once the inoculum had dried on the surface. Finally, the survival of SARS-CoV-2 on skin was assessed, showing a rapid decay at higher temperatures, with a half-life ranging from 2.8 to 17.8 hours depending on the temperature. These findings enhance our understanding of viral transmission via fomites and inform public health strategies to reduce the risk of SARS-CoV-2 transmission through surface contact.